Potential of waste flowers used as feed additive on the performance of goat kids - WADHWA, M; BAKSHI, M P S (The Indian Journal of Animal Sciences, 2021)
The present study was conducted to assess the impact of temple waste flowers as feed additive on the growth of goat kids. Marigold (Calendula officinalis) flowers constituted the bulk of WFs with negligible red roses (Rosa indica L). Marigold flowers as compared to rose flowers contained high (P